Analysis of Surety Bond Insurance Products at PT Bumiputeramuda General Insurance 1967 Medan Branch - Hanin, Fadya; Nurbaiti; Rahmani, Nur Ahmadi Bi (Ilomata International Journal of Management, 2024)
Surety Bond is an agreement between two parties, namely surety and principal. In this agreement, the surety submits a guarantee to the principal for the benefit of the obligee. If the principal fails or neglects to fulfil its obligations in accordance with the agreement with the obligee, the surety is responsible to the obligee to fulfil the principal's obligations. The purpose of this research is about the mechanism and application of surety bond principles in minimising the problems that will occur. The approach used in this research is qualitative analysis with descriptive method, which is intended to understand how the phenomenon experienced by the object of research. The results of this study explain that PT Bumiputeramuda General Insurance 1967 is one of the companies that has a surety bond product with a good implementation mechanism and applies several principles, namely the principle of togetherness, the principle of a three-party agreement, the principle of attachment, the principle of limitation of liability, the principle of legal defence, the principle of indemnity, the principle of additional / complementary contracts. This research also has implications for researchers and academics in the field of insurance. The findings of this research can be a reference material for further research on surety bond insurance products. In addition, this research can also be an input for academics to develop an educational curriculum on surety bond insurance products.